2016
DOI: 10.1016/j.soilbio.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Land-use and land-cover effects on soil microbial community abundance and composition in headwater riparian wetlands

Abstract: Headwater riparian wetlands are relatively small in size but functionally significant as expected "hot spots" of microbial activity in the landscape. Despite their roles as biogeochemical drivers, little is known about how microbial communities in headwater riparian wetlands are affected by surrounding land-uses and land-covers (LULCs). The primary objective of this study was to determine if and how wetland soil microbial abundance and community composition varied as a function of landscape metrics as mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 158 publications
0
32
0
Order By: Relevance
“…Moon et al. () found that 93% of variability in microbial biomass across these sampling blocks could be explained by soil organic matter content and mineral soil clay content (Fig. A).…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…Moon et al. () found that 93% of variability in microbial biomass across these sampling blocks could be explained by soil organic matter content and mineral soil clay content (Fig. A).…”
Section: Methodsmentioning
confidence: 94%
“…To construct our MHIs, we used soil properties that had been previously correlated with microbial biomass and composition from Moon et al. (); in this concurrent study, microbial community composition data were collected at a subset of the 1‐m 2 sampling blocks ( n = 42) across our eight sites using phospholipid fatty acid analysis. Moon et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations